Terapi Komplementer Yoga Membantu Mengatasi Fatigue Pasien Kanker Payudara - Indah Indreani Sari; Riri Maria; Agung Waluyo (Journal of Telenursing (JOTING), 2021)
This study aims to determine whether yoga can reduce the fatigue experienced by cancer patients, especially breast cancer. The research method uses an online search for library sources using databases such as Sage, Pubmed and Springer with predetermined keywords. Literature searches are limited from 2017 to 2020 in English. The results obtained were six research articles analyzed. The results showed that yoga was considered to help overcome fatigue in breast cancer patients after undergoing treatment therapy. In conclusion, yoga practice can reduce fatigue and improve the quality of life of breast cancer patients to maximize the treatment process. Keywords: Breast Cancer, Fatigue, Yoga Therapy